رسالة في توجيه قوله تعالى:( إِنَّ أَكْرَمَكُمْ عِنْدَ اللَّهِ أَتْقَاكُمْ) لإبن آدم البالكي (ت 1237ه) - الكوردي, وسو ملا زبير وسوالبرزيوي النقشبندي; الكوردي, ملامحمد ملازبيروسوالبرزيوي النقشبندي (Tobruk University Journal of Social and Human Sciences, 2024)
This research deals with the study and investigation of a manuscript of the famous science of Islam (Ibn Adam Al-Balaki Al-Kurdi).    The first section of the research deals with the study of the life of this venerable scientist since his birth and other stages of his life until death.This research deals with the study and investigation of a manuscript of the famous science of Islam (Ibn Adam Al-Balaki Al-Kurdi).    The first section of the research deals with the study of the life of this venerable scientist since his birth and other stages of his life until death.The second topic includes the investigation of a manuscript on him showing the superiority of the great companion Abu Bakr Al-Siddiq (may God be pleased with him) over the Prophet, may God bless him and grant him peace, and his priority in the caliphate through - citing and analyzing noble Quranic verses, in response to Shiite extremists who claim that the Imam has ended (the generosity of God). ). face) is the firstThe second topic includes the investigation of a manuscript on him showing the superiority of the great companion Abu Bakr Al-Siddiq (may God be pleased with him) over the Prophet, may God bless him and grant him peace, and his priority in the caliphate through - citing and analyzing noble Quranic verses, in response to Shiite extremists who claim that the Imam has ended (the generosity of God). ). face) is the first